Applications of ocean currents data from high-frequency radars and current profilers to search and rescue missions around Taiwan. (20th November 2019) - Shen, Yung-Ting; Lai, Jian-Wu; Leu, Li-Guang; Lu, Yi-Chieh; Chen, Jau-Ming; Shao, Huan-Jie; Chen, Hsien-Wen; Chang, Kuo-Tung; Terng, Chuen-Teyr; Chang, Yu-Chia; Tseng, Ruo-Shan
ABSTRACT: To enhance the immediacy and accuracy of search and rescue missions conducted by Taiwan Coast Guard Administration (TCGA), this study examines the characteristics of ocean currents and estimates the drifting trajectory of objects for two cases of marine incidents. Two methods are used to predict object's drift tracks: the first one is simply calculating the advection driven by currents and the second method adopts a Monte Carlo based software, SARMAP. Ocean currents data from a high-frequency radar system comprised of 18 radar units surrounding Taiwan supplemented by bottom-mounted Acoustic Doppler Current Profilers (ADCP) data and wind data are used as the primary oceanic environment data. The estimated ending points of drifting for both cases of missing persons in water by using both methods are consistent with the actual recovery locations. Our analyses demonstrate that ocean currents data, if properly used, can be very useful for rapid response in marine search and rescue.